Analisis Sequential Pattern Mining untuk Menggali Informasi Proses Belajar pada Media Pembelajaran Aritmatika - Rudi Gunawan; Ahmad Afif Supianto; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The application of educational technology is often used to support the learning process, one of the media of learning arithmetic. The use of learning media in the actions of the student learning process that has been carried out can store data in the data log. Data log on the sequence of student learning processes that have been generated need to be done information processing and analysis to identify the same learning patterns to help teachers provide appropriate feedback. This research aims to utilize data log from arithmetic learning media by using sequential pattern mining methods used to extract useful information from the student's learning process while working on problems. The algorithm used is Sequential PAttern Discovery using Equivalent classes (SPADE). The SPADE algorithm is applied to identify the same learning patterns based on student learning activities when using the learning media. Furthermore, learning patterns that have been successfully extracted will be analyzed for the same learning patterns based on the category of students' ability to solve problems. Based on the results of implementation and analysis that has been done on 17 problems that have been successfully processed in arithmetic learning media, 6 patterns of learning activities are produced that vary at each problem and level, which are: pattern 1, pattern 2, pattern 3 , pattern 4, pattern 5, and pattern 6. Each pattern requires different feedback to optimize learning progress.